All the gallant men [large type] : an American sailor's firsthand account of Pearl Harbor - Stratton, Donald, 1922-2020; Gire, Ken (HarperLuxe, an imprint of HarperCollinsPublishers, 2016)
A memoir by a USS Arizona survivor describes his experience of the attacks that left him with burns over more than sixty-five percent of his body, his resolve to reenter service after a grueling recovery, and his contributions to some of the Pacific's most violent battles. --Publisher.